2022
DOI: 10.35784/bud-arch.3150
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of effectiveness of selected adaptation actions to climate change. The example of the New Centre of Lodz.

Abstract: The increasing average annual temperature value is observed in many cities around the world. More and more often, not only the Southern Europe inhabitants, but also those from the Central and Northern Europe are exposed to thermal stress. Nature Based Solutions (NBS) play a key role in mitigation, i.e. the process of alleviating the negative effects of climate change in highly urbanized areas. The main objective of this study is to answer the question whether the planned spatial activities involving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…According to the conclusions drawn from these studies, utilising publicly available environmental data collected by meteorological stations allows for a simplified assessment of thermal comfort or discomfort. For the New Łódź Centre, using ENVI-met software, it was found that Nature-Based Solutions strategies contribute to improving air temperature, perceived humidity temperature, and the thermal comfort index PET [32]. The impact of new construction on wind speed and direction was observed, affecting the temperature perception, which would be different with a different building orientation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the conclusions drawn from these studies, utilising publicly available environmental data collected by meteorological stations allows for a simplified assessment of thermal comfort or discomfort. For the New Łódź Centre, using ENVI-met software, it was found that Nature-Based Solutions strategies contribute to improving air temperature, perceived humidity temperature, and the thermal comfort index PET [32]. The impact of new construction on wind speed and direction was observed, affecting the temperature perception, which would be different with a different building orientation.…”
Section: Literature Reviewmentioning
confidence: 99%